Does data analytics use improve firm decision making quality? The role of knowledge sharing and data analytics competency - Ghasemaghaei, Maryam (Decision Support Systems, 2019)
Despite the huge investment in data analytics tools, the necessary conditions required to obtain benefit from such investment deserves close investigation. In this study we utilize the knowledge-based view and data analytics competency literature to address two important research questions: (1) Does knowledge sharing have a mediating role on the impact of data analytics usage on the quality of firm decisions?; and (2) What is the role of data analytics competency in enhancing the quality of firm decisions through increasing knowledge sharing? Survey data collected from top and middle-level managers from 133 U.S.-based firms indicates that: the impact of data analytics use on the quality of firm decisions is fully mediated by knowledge sharing; the impact of knowledge sharing on firm decision quality is not significant and it is moderated by data analytics competency; and data analytics competency does not moderate the impact of data analytics use on knowledge sharing. Collectively, the findings provide a theory-based understanding of how data analytics use improves firm decision quality. The results also provide actionable guidelines for firms regarding the critical resources they need to invest in order to obtain benefits from using data analytics tools. •Using data analytics significantly improves knowledge sharing within firms.•Knowledge sharing fully mediates data analytics usage impact on decision quality.•Knowledge sharing does not necessarily improve firm decision quality.•Data analytics competency moderates knowledge sharing impact on decision quality.